2006
DOI: 10.1248/bpb.29.211
|View full text |Cite
|
Sign up to set email alerts
|

Anti-asthmatic Activity of an Ethanol Extract from Saururus chinensis

Abstract: As an attempt to find bioactive medicinal herbs exerting anti-asthmatic activity, the effects of an ethanol extract from the parts of Saururus chinensis were evaluated in both in vitro and in vivo. The ethanol extract of S. chinensis (ESC) inhibited generation of the cyclooxygenase-2 (COX-2) dependent phases of prostaglandin D 2 in bone marrow-derived mast cells in a concentration-dependent manner with an IC 50 value of 14.3 m mg/ml. ESC also inhibited leukotriene C 4 production with an IC 50 value of 0.3 m mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Its aerial portion has been used in Korean folk medicine for the treatment of edema, gonorrhea, jaundice, and several inflammatory diseases. 10) Studies have shown that S. chinensis has various activities, including anti-inflammatory, anti-oxidant, 11,12) antiangiogenic, 13) anti-asthmatic, 14) and anti-hypertensive 15) activities, as well as therapeutic activity against atopic dermatitis. 16) Among the bioactive compounds isolated from S. chinensis, manassantin A is a major phytochemical composition that has various biological activities, including anti-inflammatory, neuroleptic, and human acyl-CoA : cholesterol acyltransferase (ACA T) inhibitory activities.…”
mentioning
confidence: 99%
“…Its aerial portion has been used in Korean folk medicine for the treatment of edema, gonorrhea, jaundice, and several inflammatory diseases. 10) Studies have shown that S. chinensis has various activities, including anti-inflammatory, anti-oxidant, 11,12) antiangiogenic, 13) anti-asthmatic, 14) and anti-hypertensive 15) activities, as well as therapeutic activity against atopic dermatitis. 16) Among the bioactive compounds isolated from S. chinensis, manassantin A is a major phytochemical composition that has various biological activities, including anti-inflammatory, neuroleptic, and human acyl-CoA : cholesterol acyltransferase (ACA T) inhibitory activities.…”
mentioning
confidence: 99%
“…Activity-guided chromatographic separation of 80% EtOH extract led to isolation of eleven compounds including three active neolignans (1-3), four flavonoids (4-7), and four aristolactams (8)(9)(10)(11). The structures of 1-11 were identified as manassantin A (1), 27,28) manassantin B (2), 29) (−)-saucerneol (3), 29,30) quercetin-3-O-β-Dglucuronopyranoside (4), 31) quercitrin (5), 32) 33) isoquercitrin (7), 34) saurolactam (8), 35) aristolactam AII (9), 36) piperumbellactam B (10), 37) and aristolactam BII (11) 36) by analysis of spectroscopic data including 1 H-and 13 C-NMR data as well as by comparison of their spectroscopic data with the values reported in the literature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1) Previous pharmacological studies on S. chinensis have reported that its extracts have anti-inflammatory, anti-oxidant, anti-asthmatic, and cytotoxic activities. [2][3][4][5][6][7][8][9][10] Phytochemical investigations on this plant have reported that it contains several types of secondary metabolites, such as lignans, neolignans, aristolactams, and flavonoids [11][12][13] that are associated with anti-inflammatory, antioxidant, cytotoxic, anti-cancer, anti-human immunodeficiency virus (HIV), and anti-Acyl-CoA : cholesterol acyltransferase (ACAT)-1, 2 activities. [14][15][16][17][18][19][20][21][22][23][24][25] A number of studies demonstrated that the compounds derived from medicinal herbs play an important role in the anti-cancer activity and have been developed as new anti-cancer drugs.…”
mentioning
confidence: 99%
“…Mice underwent ovalbumin (OVA) sensitization and challenge using an earlier protocol with slight modifications [3,10,22]. OVA (100 μg/ml in saline, sterile filtered) was mixed with an equal volume of 0.1% (w/v) aluminum potassium phosphate (alum; Sigma), and the pH adjusted to 6.5 with 10 N NaOH.…”
Section: In Vivo Model and Immunohistochemistrymentioning
confidence: 99%